1997
DOI: 10.1002/elan.1140090914
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic oxidation of ascorbic acid using benzoquinone as a mediator

Abstract: Benzoquinone (BQ) in solution catalyses the electrochemical oxidation of ascorbic acid (AH,) at basal plane graphite (BPG) electrode. The overpotential for AH2 decreases by 120mV at pH7.3 in presence of BQ as compared to the potential without BQ. A simultaneous increase in anodic current in the cyclic voltammogram of BQ as a function of AHZ forms the basis of a sensor for AH2. The kinetics for the reaction between AH2 and BQ have been determined by cyclic voltainmetric data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…38 Additionally, note that BQ plays an important role in various biological redox processes and owing to its large electron affinity it is commonly employed as a redox mediator within electrochemistry. 39,40 The electrochemical properties of the electrode materials of interest were first characterised with regards to our analyte (50 mM BQ in pH 7 PBS), where as depicted in Fig. 7 the typical cyclic voltammetric responses obtained, when utilising unmodified EPPG and BPPG electrodes and EPPG and BPPG electrodes following modification with 40ng of graphene, exhibited voltammetric peaks (E P red ) at ca.…”
Section: Resultsmentioning
confidence: 99%
“…38 Additionally, note that BQ plays an important role in various biological redox processes and owing to its large electron affinity it is commonly employed as a redox mediator within electrochemistry. 39,40 The electrochemical properties of the electrode materials of interest were first characterised with regards to our analyte (50 mM BQ in pH 7 PBS), where as depicted in Fig. 7 the typical cyclic voltammetric responses obtained, when utilising unmodified EPPG and BPPG electrodes and EPPG and BPPG electrodes following modification with 40ng of graphene, exhibited voltammetric peaks (E P red ) at ca.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of electron mediator concentration on the performance of the d-fructose biosensor was also studied using 1 3 10 23 mol l 21 d-fructose at pH 6.7. In this case, the best response was found between 2 3 10 23 mol l 21 and 3 3 10 23 mol l 21 [Fe(CN) 6 ] 32 . Considering that [Fe(CN) 6 ] 32 acts as an electron transfer reagent, the rate of FDH/PQQH 2 oxidation increases markedly with the increase of [Fe(CN) 6 ] 32 concentration up to 2 3 10 23 mol l 21 , as does the current.…”
Section: Effect Of the [Fe(cn) 6 ] 32 Concentrationmentioning
confidence: 91%
“…l-Ascorbate is a more complex redox system than [Fe(CN) 6 ] 3/42 , since it involves two electrons and either one or two protons, depending on the pH. 32 Previous studies 27 have shown that the voltammetric oxidation peak shape depends on the relative rates of the two electron transfers, both of which are potential dependent. Nevertheless, anodic E p is a reliable indicator of changes in the oxidation rate caused by graphite surface modification.…”
Section: Electrochemistry Of the Basic Composite Transducermentioning
confidence: 99%
“…Murthy et al [28,29] used benzoquinone as a mediator to examine whether quinone derivatives would mediate the oxidation of ascorbic acid. They found that benzoquinone catalyzed the electrochemical oxidation of ascorbic acid at a basal plane graphite electrode.…”
Section: Oxidation Of Ascorbic Acid With Rutin In Lipid Filmmentioning
confidence: 99%